Pizza for Pia - Groban, Betsy (Ready-to-read. Star reader!, 2024)
Pia’s pop, Pete, is making pizza for Pia. Pizza is easy. Pizza is cheesy. Pia’s family says pizza is perfect. Everyone loves pizza…right?